Analisis Marginalisasi dan Diskriminasi Tokoh Nyai Ontosoroh dalam Roman Bumi Manusia Karya Pramoedya Ananta Toer - Wawan Setiawan; Rosmini Madeamin; Nurcholis Nurcholis (Pusat riset dan Inovasi Nasional, 2022)
The aims of this research include: (1) To find out the forms of marginalization and discrimination experienced by the character Nyai Ontosoroh in Pramoedya Ananta Toer's Romance of the Earth of Mankind. (2) To find out the form of resistance of the character Nyai Ontosoroh in Pramoedya Ananta Toer's Romance of the Earth of Mankind. This type of research is descriptive qualitative. The source of data obtained from this research is the book Earth of Mankind by Pramoedya Ananta Toer as primary data. Meanwhile, secondary data consists of information and references obtained scientifically from books, articles, the internet and mass media related to this research. The data collection technique used library, listening and note-taking techniques through critical discourse analysis developed by Sara Mills. The research results show that: (1) There are 6 data on marginalization experienced by the character Nyai Ontosoroh in the novel Earth of Mankind. In the family realm, the father's restriction/marginalization of rights and freedoms has made him a nyai or concubine (purchased slave). (2) There are 8 data on discrimination experienced by Nyai Ontosoroh. In the public sphere, she is seen by the general public as a woman who has no morals and is always looked down upon. (3) there are 11 data on the resistance of the figure Nyai Ontosoroh. Nyai Ontosoroh appears as the antithesis of the bad views about Nyai-Nyai. Nyai Ontosoroh emerged as the first Indigenous woman to fight European legal authority in defending her rights to her children and company.